2021
DOI: 10.1093/eurjpc/zwab025
|View full text |Cite
|
Sign up to set email alerts
|

Visual acuity and risk of overall, injury-related, and cardiovascular mortality: the Kangbuk Samsung Health Study

Abstract: Aims  The associations of visual impairment (VI) with cardio-metabolic risk factors have been reported but its association with cardiovascular mortality remains uncertain. Therefore, we evaluated the association of visual acuity (VA) with overall, injury-related, and cardiovascular mortality. Methods and results A cohort study was performed in 580 746 Korean adults (average age, 39.7 years) who were followed for a median of 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…VI may result in reduced mobility and communication skills [58], twice the risk of falls [59], and high risks of hip fractures [60], depression [61,62], and emotional distress [63,64]. Furthermore, high mortality and injury rates correlated in a population with VI [65,66]. Thus, VI limits one's independence, lowers QOL, shortens one's life in terms of physical and mental health, and has a socioeconomic impact by lowering employment rates, possible social isolation, and higher use of medical expenses [67].…”
Section: Discussionmentioning
confidence: 99%
“…VI may result in reduced mobility and communication skills [58], twice the risk of falls [59], and high risks of hip fractures [60], depression [61,62], and emotional distress [63,64]. Furthermore, high mortality and injury rates correlated in a population with VI [65,66]. Thus, VI limits one's independence, lowers QOL, shortens one's life in terms of physical and mental health, and has a socioeconomic impact by lowering employment rates, possible social isolation, and higher use of medical expenses [67].…”
Section: Discussionmentioning
confidence: 99%
“…Several other studies have shown that exposure to beta-blockers can also increase cataract formation because it can increase intracellular levels of cyclic adenosine monophosphate, resulting in the modification of lens proteins. 18,19,20 A study by Bautista et al has found that elevated plasma levels of IL-6 and TNF-a occur in patients with hypertension, which is closely associated with an intense systemic inflammation resulting in elevated levels of C-reactive protein, hence triggering cataract development. Hypertension has also been reported to cause a conformational change in the lens capsule, thereby interfering with potassium ion transport in the lens epithelial cells.…”
Section: Prasad Et Al Filho Et Al and LI Et Al Explained That The Pha...mentioning
confidence: 99%
“…The participants presenting VA while wearing their own spectacles was measured for each eye using Early Treatment Diabetic Retinopathy Study (ETDRS) scales placed at a distance of 3 m [30]. The presenting VA (either VA with naked eye vision or with own spectacle) was evaluated because it reflects real-world VA [31].…”
Section: Data Collectionmentioning
confidence: 99%